KARAKTER KERJASAMA PESERTA DIDIK DALAM PEMBELAJARAN PENJASORKES DI MADRASAH IBTIDATYAH ISLAMIYAH PONTIANAK - Marwansyah, Marwansyah; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ This study aimed to determine the character of student cooperation in physical education learning in Madrasah Ibtidaiyah Islamiyah Pontianak. The method was used descriptive method, the form of research is survey research. The research sample is class IV A as many as 25 students. The data collection technique was used the observation sheet. Data were analyzed by descriptive analysis and using percentage descriptive tests.From the results of the research carried out, it can be concluded that the character of cooperation between students in class IV A Madrasah Ibtidaiyah Islamiyah Pontianak in Penjasorkes is good. This can be seen from the average percentage based on the aspect of indicators observed and carried out by students in Penjasorkes to see the character of cooperation that is equal to 81%. Although overall the character of student cooperation in Penjasorkes was good, but some aspects of the indicator have not been well done based on observations, including: helping friends who have problems only reaching 68%, admitting mistake only reaching 56%, preparing teaching and learning processes only reaching 60% , being able to control themselves only reached 52%, and giving ideas only reached 44%.Â Keywords: Character, Cooperation